The bargain [videorecording (DVD)] - Barker, Reginald; Burke, J. Frank (John Franklin), 1867-1918; Williams, Clara, 1888-1928; Sherry, Barney, 1872-1944 (Alpha Home Entertainment, 2010)
"Notorious Jim Stokes, "The two-gun man," is badly wounded following a botched hold-up. His unconscious body is discovered by Phil Brent, a prospector. While recovering from his wounds, Jim falls in love with his nurse, Phil's lovely daughter Nell, and the two are wed. When the sheriff catches wind of his whereabouts, Jim is forced to flee from his young wife, and head for the border. Although the sheriff manages to take Jim prisoner, fate will intervene and cause the two enemies to strike a terrible bargain, one that will test the mettle of both of their souls."--Container.